2017
DOI: 10.4172/2157-7579.1000435
|View full text |Cite
|
Sign up to set email alerts
|

Expert Views on Effectiveness, Feasibility, and Implementation of Biosecurity Measures for Mitigating Tier 1 Disease Risks in the U.S. Swine, Beef Cattle, and Dairy Industries

Abstract: Understanding disease transmission routes and implications for biosecurity is critical to mitigating livestock disease outbreaks and maintaining efficient and profitable production. The goal of biosecurity is to eliminate pathogen exposure and minimize endemic pathogen impact, particularly important for foreign animal diseases that threaten U.S. animal health and the economy. We elicit swine, beef cattle, and dairy expert views on the effectiveness, feasibility, and implementation of both biosecurity measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Beliefs regarding how feasible implementation of each biosecurity practice is on his/her operation likely influences a producer's motivation to implement, as some measures could be perceived impractical or impossible (2022). Relationships between feasibility ratings and biosecurity practice implementation were investigated using cross-tabulations (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Beliefs regarding how feasible implementation of each biosecurity practice is on his/her operation likely influences a producer's motivation to implement, as some measures could be perceived impractical or impossible (2022). Relationships between feasibility ratings and biosecurity practice implementation were investigated using cross-tabulations (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Results indicate biosecurity adoption is positively related to risk reduction and negatively related to costs. Wu et al (2017) has shown that some under-implemented biosecurity measures are both highly effective (e.g., extent of risk reduction if implemented) and highly feasible (e.g., practicality of affordable implementation) for mitigating Tier 1 disease risks. Our survey indicates that one reason behind the low implementation of recommended biosecurity measures may be their corresponding costs.…”
Section: Discussionmentioning
confidence: 99%
“…These factors are mentioned in many discussions of biosecurity adoption and compliance (Hennessy, 2007a(Hennessy, , 2007b(Hennessy, , 2008Horan, Fenichel, Wolf, & Gramig, 2010;Reeling & Horan, 2014;Wu, Schulz, Tonsor, & Smith, 2017).…”
Section: Questionnaire Designmentioning
confidence: 99%
“…Compliance with onfarm biosecurity practices is influenced by various sociopsychological factors (9,10). These include the characteristics of disease risk factors and their associated costs to implement or comply with these practices (11), how the risk of diseases is communicated and perceived (12), and heuristics used to inform biosecurity judgment (13)(14)(15)(16)(17). Motivation and conditions of such decisions might also vary at tactical (i.e., decision-making at the owner or operator level) and operational (i.e., decisionmaking at the on-farm worker level) levels (15,16) and across different populations.…”
Section: Introductionmentioning
confidence: 99%